What type of economy Russia needs - L. I. Kochurova; Yu. N. Kleshchevskiy; E. I. Kharlampenkov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article proves inevitability of market management of national economy. The authors introduced in academic circulation such notions as ‘business market’ and ‘developed market.’ Serious attention is paid to the role of private property in life of society and organization of national economy. Drawbacks of national economy management in soviet times were shown, incompetence of party leaders was highlighted and this resulted in the fact that ways of coordinating industrial relations with economic laws were not found. The soviet power was not able to use market laws in the interests of the country. Party leaders were not eager to understand the market theory, as market was denied. Reforms were ineffective due to this reason. Today Russia is facing the necessity to choose strategy for the future: it could be an inertial way of neo-liberal reforms and degradation of scientific potential or mobilization of intellectual resources aiming at economy restructuring on the basis of developed market with the leading role of state. The quality of state governance can help renew social sphere, achieve sustainable growth in the standard of living, where the leading role will belong to science of life, man and society.